The Influence of Obliquely Propagating Monsoon Gravity Waves in the Southern Polar Summer Mesosphere After Stratospheric Sudden Warmings in the Winter Stratosphere. Issue 5 (5th March 2021) - Alexandre, D.; Thurairajah, B.; England, S. L.; Cullens, C. Y.
Abstract: Oblique propagation of gravity waves (GWs) refers to the latitudinal propagation (or vertical propagation away from their source) from the low‐latitude troposphere to the polar mesosphere. This propagation is not included in current gravity wave parameterization schemes, but may be an important component of the global dynamical structure. Previous studies have revealed a high correlation between observations of GW pseudomomentum flux (GWMF) from monsoon convection and Polar Mesospheric Clouds (PMCs) in the northern hemisphere. In this work, we report on data and model analysis of the effects of stratospheric sudden warmings (SSWs) in the northern hemisphere, on the oblique propagation of GWs from the southern hemisphere tropics, which in turn influence PMCs in the southern summer mesosphere. In response to SSWs, the propagation of GWs at the midlatitude winter hemisphere is enhanced. This enhancement appears to be slanted toward the equator with increasing altitude and follows the stratospheric eastward jet. The oblique propagation of GWs from the southern monsoon regions tends to start at higher altitudes with a sharper poleward slanted structure toward the summer mesosphere. The correlation between PMCs in the summer southern hemisphere and the zonal GWMF from 50°N to 50°S exhibits a pattern of high‐correlation coefficients that connects the winter stratosphere with the summer mesosphere, indicating the influence of Interhemispheric Coupling mechanism. Temperature and wind anomalies suggest that the dynamics in the winter hemisphere can influence the equatorial region, which in turn, can influence the oblique propagation of monsoon GWs. Plain Language Summary: Propagation of waves throughout the Earth's atmosphere is a key phenomenon to understanding atmospheric dynamics, as it changes temperature, pressure, density, and composition. Due to the exponentially decreasing density, the amplitude and energy carried by these waves increase exponentially as they propagate vertically. When the waves break, their energy is released and transferred to the background flow. Gravity waves (GWs) can propagate up to the middle atmosphere but are too small to be resolved by most global‐scale atmospheric models. The deep convection from monsoon regions is known to be a major source of mesospheric GWs and previous studies on summer northern hemisphere have shown that monsoon GWs tend to propagate obliquely from the low‐latitude stratopause up to the high‐latitude mesopause. We focus this study on the summer southern hemisphere and the Interhemispheric Coupling (IHC) between the summer mesopause, where Polar Mesospheric Clouds (PMCs) form, and the winter stratosphere where sudden warmings occur. PMCs are excellent indicators of atmospheric changes. Their correlations with wind, temperature, and GW pseudomomentum flux highlight the consequences of anomalies in the winter stratosphere, such as warmings, on the oblique propagation of GWs that influence the PMC formation in the summer southern hemisphere. Key Points: Polar Mesospheric Clouds in the southern hemisphere can be influenced by obliquely propagating monsoon gravity waves Stratospheric sudden warmings enhance the GW propagation at the midlatitude winter hemisphere which appear to be slanted equatorward Stratospheric sudden warmings appear to alter the GW momentum flux distribution along the oblique GW propagation path in summer hemispheres